Queer between the covers : histories of queer publishing and publishing queer voices - Kassir, Leila; Espley, Richard (Senate House Library, University of London Press, 2021)
Queer Between the Covers presents a history of radical queer publishing and literature from 1880 to the modern day. Chronicling the gay struggle for acceptance and liberation, this book demonstrates how the fight for representation was often waged secretly between the covers of books at a time when public spaces for queer identities were limited. The chapters provide an array of voices and histories from the famous, Derek Jarman and Oscar Wilde, to the lesser-known and underappreciated John Wieners and Valerie Taylor. It includes first-hand accounts of seminal moments in queer history, including the birth of Hazard Press and the Defend Gay's the Word Bookshop campaign in the 1980s. The book demonstrates how the queer community could be brought together through shared literature. The works discussed show the imaginative and radical ways in which queer texts have fought against censorship and repression and could be used as a tool for political organisation and production. A fascinating and poignant analysis of some key historic moments for queer lib in publishing and book history, this is an essential read for those interested in how LGBTQ people throughout modernity have used literature as an important forum for self-expression and self-actualisation when spaces and sites for queer expression were taboo.